PERKAWINAN USIA MUDA DI KELURAHAN SOASIO KOTA TIDORE KEPULAUAN PROPINSI MALUKU UTARA - Daud, Ismail (Universitas Sam Ratulangi, 2016)
One of the most important transition in human life is the passage from adolescence to adulthood and raise a family which is marked by marriage. Marriage young age generally was an institution to bind two humans the opposite sex in the ground in one family bonds. Marriage in terms of culture the community Tidore and especially Kelurahan Soasio is an obligatory for every man as a form of gratitude them for Allah SWT who created man in pairs creatures believe and fear, and holding firmness of will values marriage and responsibilities for those who will family and involved in one whole a large family and the unification of family. Research aims to understand the marriage a young age because the intercommunication that causes pregnant out of wedlock and there are also because a specific factor of a pair who performs marriage a young age, the majority of which teenager who are both in are out of school we have dropped out of school. Methods used is a description of qualitative. Promiscuity factor in this case is that teens who performs making love out of wedlock and then pregnant and to cover their deeds parents forced to fecundate to close disgrace that they have done and to keep the good name of the family. Freedom intercommunication between different of the sexes in a juvenile Kelurahan Soasio easily usual witnessed in daily life. Keywords: marriage, teenager, pregnant